2021
DOI: 10.4274/jcrpe.galenos.2021.2020.0303
|View full text |Cite
|
Sign up to set email alerts
|

Midkine: Utility as a Predictor of Early Diabetic Nephropathy in Children with Type 1 Diabetes Mellitus

Abstract: Objective: This study aimed to assess the role of serum midkine (MK) as a biomarker for early detection of diabetic nephropathy in children with type 1 diabetes mellitus (T1DM) before microalbuminuria emerges. Methods: A total of 120 children with T1DM, comprising 60 microalbuminuric patients (Group 1), 60 normoalbuminuric patients (Group 2), and 60 healthy participants as a control group (Group 3) were included. Detailed medical history, clinical examination, and labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[697], IL18 [698], CYGB (cytoglobin) [636], EGF (epidermal growth factor) [699], TRPM2 [700], BANK1 [701], SORT1 [643], HSPG2 [645], NOX4 [702], MYH9 [703], TRPV4 [704], B4GALNT1 [705], LAG3 [706], CACNA1C [654], LRP5 [707], PIM1 [658], MDK (midkine) [708], CA2 [709], TRPC6 [710], CYP2D6 [711] and STAT4 [712] might be a biological target of type 1 diabetes mellitus. CCK (cholecystokinin) [713], IL33 [714], IRF4 [715], CXCL8 [716], MMP3 [717], DDIT4L [718], KL (klotho) [719], CXCL6 [87], CXCL1 [720], STC1 [721], PDK4 [722], RAB27B [723], CXCL5 [724], GPRC5A [725], TXNIP (thioredoxin interacting protein) [726], RAB3B [727], HSPA5 [728], DKK1 [93], NAMPT (nicotinamidephosphoribosyltransferase) [729], TNFAIP3 [730], GHR (growth hormone receptor) [731], ANXA1 [732], CD40 [733], KITLG (KIT ligand) [734], SMURF2 [735], NRG1 [684], GCLC (glutamate-cysteine ligase catalytic subunit) [685], NPHP1 [736], EPOR (erythropoietin receptor) [737], ADK (adenosine kinase) [738], SAA1…”
Section: Discussionmentioning
confidence: 99%
“…[697], IL18 [698], CYGB (cytoglobin) [636], EGF (epidermal growth factor) [699], TRPM2 [700], BANK1 [701], SORT1 [643], HSPG2 [645], NOX4 [702], MYH9 [703], TRPV4 [704], B4GALNT1 [705], LAG3 [706], CACNA1C [654], LRP5 [707], PIM1 [658], MDK (midkine) [708], CA2 [709], TRPC6 [710], CYP2D6 [711] and STAT4 [712] might be a biological target of type 1 diabetes mellitus. CCK (cholecystokinin) [713], IL33 [714], IRF4 [715], CXCL8 [716], MMP3 [717], DDIT4L [718], KL (klotho) [719], CXCL6 [87], CXCL1 [720], STC1 [721], PDK4 [722], RAB27B [723], CXCL5 [724], GPRC5A [725], TXNIP (thioredoxin interacting protein) [726], RAB3B [727], HSPA5 [728], DKK1 [93], NAMPT (nicotinamidephosphoribosyltransferase) [729], TNFAIP3 [730], GHR (growth hormone receptor) [731], ANXA1 [732], CD40 [733], KITLG (KIT ligand) [734], SMURF2 [735], NRG1 [684], GCLC (glutamate-cysteine ligase catalytic subunit) [685], NPHP1 [736], EPOR (erythropoietin receptor) [737], ADK (adenosine kinase) [738], SAA1…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell infiltration and smooth muscle cell migration produce Neointima development (Said et al, 2022). MK is involved in diabetic nephropathy, and the data show that MK speeds up the intracellular signaling network triggered by hyperglycemia in diabetic nephropathy and is involved in tubulointerstitial inflammation (Metwalley et al, 2021)…”
Section: -Kidneymentioning
confidence: 92%
“…Further, MK is closely related to a variety of kidney diseases (21). It was reported that MK is a biomarker for early detection of diabetic nephropathy in children with type 1 diabetes mellitus (T1DM) (22). In Mdk −/− mice, nephropathy was strikingly milder than Mdk +/+ mice after Streptozotocin injection (23).…”
Section: Original Articlementioning
confidence: 99%